The role of corporate communication in intelligent organizations - Lozano Oviedo, Jonathan (Cuadernos de Administración, 2019)
Intelligent organizations are characterized for having a high learning capacity, innovation, response and competitivity within its action center. However, corporate communication is also seen as a basic component of such organizations; being considered a pillar of effectivity in management within the organizational mark. The following article makes a reflexion around corporate communication and it’s underlying elements, perceiving it as an indispensable piece of management in the intelligent organizations that find success and are able to maintain themselves in high uncertain environments, competitivity, client’s demand and under a high volume of information that characterize the actual knowledge society. It emphasizes the necessity of the communication role value in this context and it poses a net mode from the effective management of corporate communication allowing development of organization intelligence.